Improving medical students' knowledge and skill in communicating with people with acquired communication disorders. (2nd November 2017) - Forsgren, Emma; Hartelius, Lena; Saldert, Charlotta
Abstract: Purpose : To explore the effects of an interactive workshop on medical students' knowledge and skill in communicating with people with acquired communication disorders. Method : Sixty-nine medical students received a lecture on acquired communication disorders. Thirty-six of these students also participated in a workshop where they practised using supportive strategies in interaction with a simulated patient with aphasia. All students completed a questionnaire exploring attitudes, confidence in knowledge and ability to suggest suitable supportive strategies pre- and post-lecture/workshop and 15 students were video recorded when interacting with a simulated patient pre- and post-workshop. Result : The results show no change in attitude in either student group, but both groups rated their confidence in knowledge as higher post-lecture/workshop. The students' ability to suggest supportive strategies post training was significantly higher only in the workshop group. Comparing post training results regarding knowledge and ability to suggest supportive strategies between the groups, higher ratings were found for the workshop group. The analysis of video recordings indicated that the students also used new supportive strategies and used strategies more frequently after the workshop. Conclusion : An interactive workshop can improve medical students' knowledge and skills in communicating with people with acquired communication disorders.